Black Panther : the intergalactic empire of Wakanda. Part two - Coates, Ta-Nehisi (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2019)
When a dissident from the Martian-conquered future, Erik Killraven, threatens to overthrow Wakanda, the disgraced prince must wager what little is left of his soul to save his people! And for years, the Maroons have lain dormant, planning the next stage of their rebellion. At last, it is time to strike - with a treasure hunt for unstable Vibranium! And with the Black Panther once again in their ranks, they're certain of victory. But what will victory cost? When the chips are down, will the Maroons rise to heroism, or are they doomed by the trauma of their past?